SANKSI HUKUM BAGI KEPALA DAERAH YANG TERBUKTI MELAKUKAN PERZINAHAN - Sujana Donandi S (Problematika Hukum, 2017)
Adultery conducted by The Head of a Region (The Head) occurs legal consequences for the head. Then , how are the legal sanction for The Head that has been proven commit to adultery? Considering there are 2 presence legal subjects namely natural person and incumbency attached to the one who act as The Head, so, how would the imposition of sanctions against The Head be? This research attempts to described how are the implementation of legal sanction that can be given to The Head proven doing adultery. This is a Normative Legal research that try to examine the implementation of legal sanvtion to The Head who been proven commit to adultery using literatures and legislation as source of analysis. The results show that The Head that has been proven commit to adultery could be sentenced with maximum 9 months in prison sanction based on article 284 KUHP and administrative sanctions of dismissal from the position based on the Act no. 23 2014 Concern on local government .